Industry, Brand, and the Role of Digital Medium - Indro Adinugroho; Didit Hersanto; Antonina Renata Putri; Steffi Hartanto; Smitha Sjahputri (Bina Nusantara University, 2018)
Rapid growth in information technology forces various industries and business owners to think strategically to reach public attention. This condition also brings the logical consequence of using online medium as their primary marketing tools. Various online medium or usually called as social media such as Twitter, Path, and Facebook have been used by numerous industries as tools to communicate their ideas, brands, and promotion to the public. Along with this condition, industries need to think strategically to develop contemporary marketing communication strategy. This research is a case analysis focusing on examining marketing communication strategy of a brand. One brand identified is Pocari Sweat, Japanese isotonic drink brand. This brand is selected due to the availability of our computer devices to track the tweets. From this study, we have concluded that in this disruption era, marketing communication strategy can be known and identified by others only by tracking their digital footprint.